Tanggung Jawab Pelaku Usaha terhadap Konsumen yang Mengalami Perbedaan Harga Antara Label Harga dan Harga Kasir di Tinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen: (Studi Kasus di Toko Suba Suka, Kota Kupang) - Cindy Sara Nauolim; Siti Ramlah Usman; Yossie M.Y. Jacob (Lembaga Pengembangan Kinerja Dosen, 2024)
The price difference between the price tag and the cashier's price that occurs at Suba Suka Store is a form of violation of consumer rights, so that legal certainty is needed to protect the rights and obligations of consumers and business actors. The formulation of this research problem are: (a) How is legal protection for consumers who experience price differences between price tags and cashier's prices according to Law Number 8 of 1999 concerning Consumer Protection? (b) What is the responsibility of business actors regarding price differences between price tags and cashier's prices experienced by consumers at Suba Suka Store, Kupang City? The objectives of this research are: (a) To determine the legal protection for consumers who experience price differences based on Law Number 8 of 1999 concerning Consumer Protection; and (b) To determine the form of responsibility of business actors in handling the problem of price differences at Suba Suka Store in Kupang City. The results showed that (a) Legal protection for consumers who experience price differences is clearly regulated, but in its implementation based on existing provisions, it has not been carried out properly because there has been no complaint to be resolved directly by the authorized party, namely BPSK at the NTT Provincial Disperindag, so that when consumers file a complaint (b) the form of responsibility of the Suba Suka Store is to provide prices according to what is found by the store, the rest is the right of consumers to decide to continue or cancel the transaction. The conclusions in this paper are: (a) The legal protection provided has not been implemented properly because it has never been resolved by the authorized party, either directly or indirectly (b) errors in the price tag and cashier's price are things that need to be paid attention to again by the Suba Suka Store to become their full responsibility to solve the problem of price differences that occur. The author's suggestions (a) it is necessary to increase supervision and provide socialization about consumer protection (b) every business actor pays more attention to replacing price tags (c) consumers are expected to be smarter and increase awareness when they realize their rights are being violated (d) to further researchers so that they can continue this research to support this thesis.